2020
DOI: 10.1523/jneurosci.2630-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

EGF and a GSK3 Inhibitor Deplete Junctional E-cadherin and Stimulate Proliferation in the Mature Mammalian Ear

Abstract: Sensory hair cell losses underlie the vast majority of permanent hearing and balance deficits in humans, but many nonmammalian vertebrates can fully recover from hearing impairments and balance dysfunctions because supporting cells (SCs) in their ears retain lifelong regenerative capacities that depend on proliferation and differentiation as replacement hair cells. Most SCs in vertebrate ears stop dividing during embryogenesis; and soon after birth, vestibular SCs in mammals transition to lasting quiescence as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Hair cell injury to the chick utricle resulted in nuclear translocation of YAP1, but we did not observe this response in the mouse utricle, even after severe epithelial injury. These results, which are consistent with findings recently reported by other investigators [34][35][36][37] , suggest that the lack of YAP1 signaling following hair cell damage may be one factor that limits the regenerative ability of the mammalian ear.…”
Section: Discussionsupporting
confidence: 93%
“…Hair cell injury to the chick utricle resulted in nuclear translocation of YAP1, but we did not observe this response in the mouse utricle, even after severe epithelial injury. These results, which are consistent with findings recently reported by other investigators [34][35][36][37] , suggest that the lack of YAP1 signaling following hair cell damage may be one factor that limits the regenerative ability of the mammalian ear.…”
Section: Discussionsupporting
confidence: 93%
“…E-cadherin is reported to activate LATS1/2 independently of MST1/2 in other epithelia (Kim et al, 2011) and is expressed at much higher levels in mammalian SCs than in those of birds, fish, and amphibians (Collado et al, 2011b;Burns et al, 2013). Pharmacologic treatments that deplete E-cadherin from striolar SC junctions also affect YAP expression and induce SC proliferation (Kozlowski et al, 2020). Here, overexpression of YAP-S127A in mammalian SCs induced upregulation of E-cadherin in what may reflect negative feedback (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…YAP-TEAD transcriptional activity can also induce negative feedback (Dai et al, 2015;Moroishi et al, 2015;Park et al, 2016). E-cadherin is reported to be a negative regulator of YAP in other epithelia (Kim et al, 2011;Benham-Pyle et al, 2015), and is hypothesized to restrict the activity of YAP in SCs of the mammalian utricle (Kozlowski et al, 2020). To test whether expression of YAP-S127A affects E-cadherin expression, we administered doxycycline to Yap-S127A 1/À ;Sox10 rtTA/1 mice and littermate controls at P1.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, we recently reported that treatments with EGF and a GSK3β inhibitor cause significant thinning of the circumferential F-actin bands in SCs throughout the sensory epithelium in utricles cultured from adult mice ( Kozlowski et al, 2020 ). With time, treatment with EGF and a GSK3β inhibitor caused depletion of E-cadherin at the junctions between SCs located within the striola and resulted in significant SC proliferation that was restricted to the striola.…”
Section: Discussionmentioning
confidence: 96%